2015
DOI: 10.3402/snp.v5.28602
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving what you intend to do from what you do: evidence for embodiment in social interactions

Abstract: Although action and perception are central components of our interactions with the external world, the most recent experimental investigations also support their implications in the emotional, decision-making, and goal ascription processes in social context. In this article, we review the existing literature supporting this view and highlighting a link between reach-to-grasp motor actions and social communicative processes. First, we discuss the most recent experimental findings showing how the social context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 105 publications
1
14
0
1
Order By: Relevance
“…More recently, the social goal of an object-directed motor action was also found to influence movement kinematics (for reviews see [26][27][28][29][30]. A number of studies have indeed revealed that an object-oriented motor action performed with a social goal, i.e.…”
Section: The Combined Effects Of Motor and Social Goals On The Kinemamentioning
confidence: 99%
“…More recently, the social goal of an object-directed motor action was also found to influence movement kinematics (for reviews see [26][27][28][29][30]. A number of studies have indeed revealed that an object-oriented motor action performed with a social goal, i.e.…”
Section: The Combined Effects Of Motor and Social Goals On The Kinemamentioning
confidence: 99%
“…Similar results have been reported by [ 23 ] who found a variation in the kinematics of the actions when placing a piece of food into the mouth of another person, compared to acts ending into a mouth-like aperture on a dummy head. Quesque et al [ 24 ] relied on a similar paradigm and demonstrated the effects of peripersonal space on hand movement kinematics performed with social intentions (but see also [ 26 ] for a similar effect in the presence of a familiar but not of an unfamiliar attendee): a hand movement took a longer time to be initiated when intended to place an object within the peripersonal-action (at reachability-distance), but not into a farther, space of a human attendee. In a similar vein, [ 31 ] found shorter hand movement duration in a competitive rather than a cooperative social context.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, while several studies proved how the kinematics of reach-to-grasp movements is affected by specific variations of factors like object position, type, size or familiarity [8][9][10][11][12][13] , kinematics modulations of reaching and grasping were found even when the same object was grasped with different intents, as for example to place or to throw it in a container 14,15 . Moreover, further modulations emerged associated to social intentions, as in the case of a movement addressed toward another individual in opposition to ourselves [16][17][18][19][20] , or when it has cooperative or competitive goals [21][22][23] . In turn, the kinematics of the observed action can modulate the reactivity of the observer's motor system [24][25][26][27][28][29] .…”
mentioning
confidence: 99%